A comparison of different hand and rotary endodontic glide path files for buckling resistance: An in vitro study - Ruchika Gupta; Pramod Mohite; Suvarna Patil; Nandita Bansal (Wolters Kluwer Medknow Publications, 2021)
Introduction: The purpose of the present study was to compare the buckling resistance between the hand files and rotary files and compare the buckling resistance between pathfinding files made out of different alloys. Materials and Method: The test instruments were divided into two major groups based on the mode of use, hand instruments and rotary instruments. These groups were further divided into six subgroups. Six subgroups of endodontic files containing three samples were tested for buckling resistance by applying load in axial direction using a universal testing machine. The maximum load required to generate a lateral elastic displacement of 1 mm was recorded for each instrument. Data were analyzed using two-way analysis of variance and Newman-Keuls multiple post hoc tests using software SPSS version 19. P value was considered < 0.05. Results: The results indicated that the buckling resistance decreased in the following order: Hand C Plus file > Rotary One G file > Hand C pilot files > Rotary ProGlider file > Hand PathFinder Carbon Steel > Rotary HyFlex Electric Discharge Machining (EDM) file. Conclusion: The stainless steel instruments (C + and C-Pilot) were more resistant to buckling than carbon steel (Pathfinder CS) and nickel-titanium instruments (ProGlider and HyFlex EDM). Buckling resistance may influence instrument's performance during the negotiation of constricted canals, and the C Plus in hand file group showed significantly better results than the other instruments tested. Metallurgy and modulus of elasticity of the instruments play a significant role in buckling resistance as One G file in rotary file group showed highest buckling resistance (conventional austenite nickel-titanium) than ProGlider (M-wire NiTi) and HyFlex (EDM + Controlled Memory).